Density and nitrifying potential of indigenous bacterial community in mangrove and seagrass in the north of Vietnam - Huyen, Le Thanh; Tuyet, Dao Thi Anh; Hiep, Le Minh; Dat, Nguyen Tien; Binh, Ha Thi; Sy, Do Trung; Hao, Do Manh (Vietnam Journal of Marine Science and Technology, 2020)
Density and nitrification potential of indigenous microorganism in mangroves (Tien Yen - Quang Ninh and Bang La - Hai Phong) and seagrass (Ha Coi, Dam Ha - Quang Ninh and Tam Giang - Thua Thien Hue) in the north of Vietnam were evaluated through 4 sampling times in the dry and rainy seasons in the years of 2017-2019. The analytical results showed that the average density of nitrifying bacteria was 4.6 ± 1.8 × 102 MPN/ml, in which the density in mangroves tended to be higher than that in the seagrass beds (P < 0.05) in both the rainy and dry seasons. The average nitrifying rate was 2.7 ± 0.6 µgN/g wet soil/hour, in which the rate in mangroves tended to be higher than that in seagrass beds in the rainy season (P < 0.05). Nitrifying density and rate are not only correlated with substrate concentration but also with other environmental factors such as P-PO4, BOD5, total phosphate in sediment and total bacterial density.